Treatment of Fabry Disease management with migalastat—outcome from a prospective 24 months observational multicenter study (FAMOUS). Issue 3 (16th March 2021) - Lenders, Malte; Nordbeck, Peter; Kurschat, Christine; Eveslage, Maria; Karabul, Nesrin; Kaufeld, Jessica; Hennermann, Julia B; Patten, Monica; Cybulla, Markus; Müntze, Jonas; Üçeyler, Nurcan; Liu, Dan; et al.
Abstract: Aims: Fabry disease (FD) is an X-linked lysosomal storage disorder caused by a deficiency of the lysosomal enzyme α-galactosidase A (GLA/AGAL), resulting in the lysosomal accumulation of globotriaosylceramide (Gb3 ). Patients with amenable GLA mutations can be treated with migalastat, an oral pharmacological chaperone increasing endogenous AGAL activity. In this prospective observational multicentre study, safety as well as cardiovascular, renal, and patient-reported outcomes and disease biomarkers were assessed after 12 and 24 months of migalastat treatment under 'real-world' conditions. Methods and results: A total of 54 patients (26 females) (33 of these [61.1%] pre-treated with enzyme replacement therapy) with amenable mutations were analysed. Treatment was generally safe and well tolerated. A total of 153 events per 1000 patient-years were detected. Overall left ventricular mass index decreased after 24 months (all: −7.5 ± 17.4 g/m 2, P  = 0.0118; females: −4.6 ± 9.1 g/m 2, P  = 0.0554; males: −9.9 ± 22.2 g/m 2, P  = 0.0699). After 24 months, females and males presented with a moderate yearly loss of estimated glomerular filtration rate (−2.6 and −4.4 mL/min/1.73 m 2 per year; P  = 0.0317 and P  = 0.0028, respectively). FD-specific manifestations/symptoms remained stable (all P  > 0.05). A total of 76.9% of females and 50% of males suffered from pain, which has not improved under treatment. FD-specific disease scores (Disease Severity Scoring System and Mainz Severity Score Index) remained stable during treatment. AGAL activities and plasma lyso-Gb3 values remained stable, although some male patients presented with increasing lyso-Gb3 levels over time. Conclusions: Treatment with migalastat was generally safe and resulted in most patients in an amelioration of left ventricular mass. However, due to the heterogeneity of FD phenotypes, it is advisable that the treating physician monitors the clinical response regularly.